Boom, Bust or Prosperity? : Managing Sub-Saharan Africa's Natural Resource Wealth - Lundgren, Charlotte (Departmental Papers; Departmental Paper ;, 2013)
Sizeable natural resource endowments and potentially large financial inflows from their extraction provide an unparalleled opportunity for economic growth and development in a growing number of sub-Saharan African countries. Empirical evidence suggests, however, that translating this resource wealth into stronger economic performance and a higher standard of living has proven challenging. Much has been written about the resource curse. This publication focuses on solutions to the challenges and outlines the main policy considerations and options in managing natural resource wealth, drawing on experience within and outside sub-Saharan Africa and referring closely to the latest analysis and policy advice in this area by the IMF, the World Bank, and leading academic research. A key feature of each chapter is a recommended reading list for those who wish additional, more in-depth material on these issues to further inform policymakers and other stakeholders on the theoretical and analytical underpinnings of the policy advice.